2006
DOI: 10.1124/dmd.105.008748
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Bile Acid Transport across Na+/Taurocholate Cotransporting Polypeptide (SLC10A1) and Bile Salt Export Pump (ABCB 11)-Coexpressing LLC-PK1 Cells by Cholestasis-Inducing Drugs

Abstract: ABSTRACT:Vectorial transport of bile acids across hepatocytes is a major driving force for bile flow, and bile acid retention in the liver causes hepatotoxicity. The basolateral and apical transporters for bile acids are thought to be targets of drugs that induce cholestasis. Previously, we constructed polarized LLC-PK1 cells that express both a major bile acid uptake transporter human Na

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
91
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(97 citation statements)
references
References 35 publications
(39 reference statements)
3
91
0
3
Order By: Relevance
“…The utility of CGamF as a convenient fluorescent probe simulating bile salt transport in various in vitro and in vivo models of different species has been demonstrated previously (Maglova et al, 1995;Bravo et al, 1998;Holzinger et al, 1998;Mita et al, 2006). Mita et al (2006) showed that CGamF as well as other fluorescent bile salt analogues were transported across LLC-PK1 cells co-expressing NTCP (SLC10A1) and BSEP (ABCB11), albeit at a substantially lower rate than the natural bile salt taurocholate. In rat and human hepatocytes, we demonstrated that CGamF is mainly accumulated by sodium-independent mechanisms that are sensitive to the OATP inhibitor rifampicin (Ye et al, 2008;Ye et al, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The utility of CGamF as a convenient fluorescent probe simulating bile salt transport in various in vitro and in vivo models of different species has been demonstrated previously (Maglova et al, 1995;Bravo et al, 1998;Holzinger et al, 1998;Mita et al, 2006). Mita et al (2006) showed that CGamF as well as other fluorescent bile salt analogues were transported across LLC-PK1 cells co-expressing NTCP (SLC10A1) and BSEP (ABCB11), albeit at a substantially lower rate than the natural bile salt taurocholate. In rat and human hepatocytes, we demonstrated that CGamF is mainly accumulated by sodium-independent mechanisms that are sensitive to the OATP inhibitor rifampicin (Ye et al, 2008;Ye et al, 2009).…”
mentioning
confidence: 99%
“…CGamF was synthesized by conjugation of 5-aminofluorescein with the carboxylic group of the natural bile acid cholylglycine yielding a fluorescent bile salt analogue (Holzinger et al, 1998). The utility of CGamF as a convenient fluorescent probe simulating bile salt transport in various in vitro and in vivo models of different species has been demonstrated previously (Maglova et al, 1995;Bravo et al, 1998;Holzinger et al, 1998;Mita et al, 2006). Mita et al (2006) showed that CGamF as well as other fluorescent bile salt analogues were transported across LLC-PK1 cells co-expressing NTCP (SLC10A1) and BSEP (ABCB11), albeit at a substantially lower rate than the natural bile salt taurocholate.…”
mentioning
confidence: 99%
“…La estrategia más común para su evaluación se basa en el uso de derivados de ácidos biliares, o bien marcados isotópicamente o bien derivados fluorescentes. [70][71][72][73][74][75][76][77] Aunque los resultados obtenidos con ácidos biliares marcados isotópicamente son muy alentadores, presentan el inconveniente de su precio y dificultad de manejo. Por ello parece más interesante poner a punto nuevos métodos que permitan el empleo de derivados fluorescentes en técnicas capaces de predecir el potencial colestásico de nuevos fármacos.…”
Section: Análisis De La Situaciónunclassified
“…El compuesto final que se obtuvo está descrito y es conocido como colilamidofluoresceína (CamF). [72,[79][80] Brevemente, la ruta sintética descrita para su preparación se basó en la condensación de la 4-aminofluoresceína comercial con el ácido cólico utilizando Así pues, partiendo de ácido cólico se puede preparar una familia de intermedios versátiles que permitan la conjugación con otros fluoróforos.…”
Section: Aminofluoresceína (Amf)unclassified
See 1 more Smart Citation